FoxO3 increases miR-34a to cause palmitate-induced cholangiocyte lipoapoptosis - Natarajan, Sathish Kumar (J Lipid Res, 2017)
Nonalcoholic steatohepatitis (NASH) patients have elevated plasma saturated free fatty acid levels. These toxic fatty acids can induce liver cell death and our recent results demonstrated that the biliary epithelium may be susceptible to lipotoxicity. Here, we explored the molecular mechanisms of cholangiocyte lipoapoptosis in cell culture and in an animal model of NASH. Treatment of cholangiocytes with palmitate (PA) showed increased caspase 3/7 activity and increased levels of cleaved poly (ADP-ribose) polymerase and cleaved caspase 3, demonstrating cholangiocyte lipoapoptosis. Interestingly, treatment with PA significantly increased the levels of microRNA miR-34a, a pro-apoptotic microRNA known to be elevated in NASH. PA induction of miR-34a was abolished in cholangiocytes transduced with forkhead family of transcription factor class O (FoxO)3 shRNA, demonstrating that FoxO3 activation is upstream of miR-34a and suggesting that FoxO3 is a novel transcriptional regulator of miR-34a. Further, anti-miR-34a protected cholangiocytes from PA-induced lipoapoptosis. Direct and indirect targets of miR-34a, such as SIRT1, receptor tyrosine kinase (MET), Kruppel-like factor 4, fibroblast growth factor receptor (FGFR)1, and FGFR4, were all decreased in PA-treated cholangiocytes. SIRT1 and MET were partially rescued by a miR-34a antagonist. Cholangiocyte apoptosis and miR-34a were dramatically increased in the liver of mice with early histologic features of NASH. Our study provides evidence for the pro-apoptotic role of miR-34a in PA-induced cholangiocyte lipoapoptosis in culture and in the liver.